Effect of Surface Machining on Energy Storing Process in Austenitic Steel Subjected to Tensile Deformation - S.P. Gadaj; J. Kaczmarek; W. Oliferuk (Engineering Transactions, 1984)
The paper presents the results of investigation of the effect of abrasive mechanical and electrochemical machining on the behaviour of the energy, storing process in austenitic steel subjected to tensile. deformation. The stored energy is found as the difference of the mechanical energy supplied to the sample and the beat released during its deformation. It has been found that the behaviour of the energy storing process in austenitic steel depends to a large extent on the applied machining technique. It is supposed that this effect is related to the increase of dislocation density due to the abrasive mechanical machining of the sample.